Antivirals Against Coronaviruses: Candidate Drugs for SARS-CoV-2 Treatment? - Santos, Igor de Andrade; Grosche, Victória Riquena; Bergamini, Fernando Rodrigues Goulart; Sabino-Silva, Robinson; Jardim, Ana Carolina Gomes (Frontiers in Microbiology, 2020)
Coronaviruses (CoVs) are a group of viruses from the family Coronaviridae that can infect humans and animals, causing mild to severe diseases. The ongoing pandemic of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) represents a global threat, urging the development of new therapeutic strategies. Here we present a selection of relevant compounds that have been described from 2005 until now as having in vitro and/or in vivo antiviral activities against human and/or animal CoVs. We also present compounds that have reached clinical trials as well as further discussing the potentiality of other molecules for application in (re)emergent CoVs outbreaks. Finally, through rationalization of the data presented herein, we wish to encourage further research encompassing these compounds as potential SARS-CoV-2 drug candidates.